(untitled) (AYUSHDHARA, 2022)
Kachnar (Bauhinia variegata) is a common drug of the Ayurvedic system of medicine used in different Ayurvedic formulation for the treatment of various ailments. Kachnar is a member of the Leguminosae family and is widely produced in the tropical regions of world and countries such as Asia, China, India, Bhutan, and Thailand. All parts of Kachnar are enriched with medicinal and nutritional efficiency including the roots, leaves, bark, stem and flowers. A class of phytochemicals like protein, amino acid, fixed oils, fats, phenolic compounds, tannins and saponins are found in Kachnar. Kachnar is used to treat goiter, pain, diabetes, hyperthyroidism, ulceration and it shows various proven Pharmacological activities such as anti-inflammatory, anti-oxidant, immune-modulatory, antibacterial, anti-diabetic, analgesic and thyroid hormone regulator activity. This review article chiefly highlights the phytoconstituents present in the Kachnar and pharmacological properties of Kachnar.